Perception of The Economics Utilization and Sustainability of Cempedik Fish (Osteochilus Spilurus) in East Belitung Regency - Ardiansyah Kurniawan; Ira Triswiyana (Faculty of Fisheries and Marine Science, Brawijaya University, 2019)
Osteochilus spilurus, which has been known to be of minimal use, is an important economical fish in East Belitung. Public perceptions related to consumption and understanding of these fish need to be known as the community's point of view in utilization and management. This study was conducted to obtain information about people’s perceptions about Cempedik Fish from the citizen and related business actors in Gantung District. Information and data collection techniques in this study were carried out with three kinds of methods, namely, interviews, observation, and discussion. Public perception of Gantung District, Belitung Timur Regency towards Cempedik Fish shows that more than 79% of respondents recognize and consume these fish with the majority of consumption obtained from trade. Season and methods of catching Cempedik fish are understood to be more than 65% of respondents. Most of them assume that the size and number of fish are not changing. But they hope protection and cultivation for the continuity of production. The limited availability of Cempedik Fish products outside the rainy season is a potential for its development as an aquaculture commodity for meeting market demands and the sustainability of populations in their natural habitats.